Investigating multilingual signs and their functional categories in a private Indonesian University - Carla Stevia Ngamelubun; Anna Marietta da Silva (Universitas Cokroaminoto Palopo, 2026)
Recently, linguistic landscape research has been extended to schools and universities given their different characteristics in comparison to other public places such as city centers, shopping centers, or tourist spots. This study aims to contribute to the existing discourse of the universityscape by investigating the features and functional categories of multilingual signage in one private university in Jakarta. The study adopted quantitative and qualitative approaches to analyze language distribution, characteristics and functional categories. Data comprised 373 photos of public signs at the research site. The study found that the multilingual signs were characterized by the presence of direct translation and blends that are addressed mostly to both local and international students as the main stakeholders. The study also discovered that the interactive category, followed by the educational category was predominant, indicating the campus’ effort to make use of multilingual public signage as an extensive communicative act directed toward their multilingual stakeholders and visitors. All in all, through its linguistic landscape, the campus demonstrates their awareness of the readers’ multilingual repertoire to promote and advocate their values and identity as well as create a mutual relationship with their stakeholders and the public in general.